2013
DOI: 10.1021/bi4007644
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target Effects of MEK Inhibitors

Abstract: The mitogen-activated protein kinases (MAPKs) ERK1/2 regulate numerous cellular processes including gene transcription, proliferation, and differentiation. The only known substrates of the MAP2Ks MEK1/2 are ERK1/2; thus, the MEK inhibitors PD98059, U0126, and PD0325901 have been important tools in determining the functions of ERK1/2. By using these inhibitors and genetically manipulating MEK, we find that ERK1/2 activation is neither sufficient nor necessary for regulated insulin secretion from pancreatic beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
(39 reference statements)
5
40
0
Order By: Relevance
“…These data suggest that ERK signaling is crucial for CK2.3 mediated mineralization. However, there is still the possibility that the ERK inhibitor PD98059 could have had off target side effects as reported earlier in a different cell line 21 . Our immunostaining data suggest that activation of ERK is important for CK2.3 signaling.…”
Section: Discussionmentioning
confidence: 89%
“…These data suggest that ERK signaling is crucial for CK2.3 mediated mineralization. However, there is still the possibility that the ERK inhibitor PD98059 could have had off target side effects as reported earlier in a different cell line 21 . Our immunostaining data suggest that activation of ERK is important for CK2.3 signaling.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, a lack of contribution of either ERK1/2 or PI3K or both to BDNF-induced neuroprotection has been suggested previously (Han and Holtzman, 2000;Hetman et al, 1999;Klö cker et al, 2000). Such discrepancies may be due to differences in the toxic stimulus, the developmental state of the tissue, and possibly also non-selective pharmacological actions of the ERK1/2 and PI3K inhibitors used (Gharbi et al, 2007;Wauson et al, 2013). For example, synaptic connectivity, which is present in our culture networks at days in vitro (DIV) 10-12 (Arnold et al, 2005;Hardingham et al, 2001) but absent in 6-to 7-day-old cultures (data not shown), is necessary for the nuclear calcium signaling and transcriptional responses to BDNF.…”
Section: Discussionmentioning
confidence: 96%
“…Further specificity testing of U0126 (at 10 µM) against over 70 protein kinases did not reveal the additional off-targets (Bain et al, 2007). However, the MEK1/2-independent offtarget effects of U0126 are documented (Bachleda and Dvorák, 2008;Dokladda et al, 2005;Evans et al, 2013;Freeman et al, 2011;Ong et al, 2015;Ripple et al, 2013;Wauson et al, 2013). For example, although neuroprotective effect of U0126 against oxidative stress was attributed to its function as a MEK inhibitor in a number of previous reports, a recent study provided evidence that 10 μM U0126 inhibited cell death, induced by a number of different oxidative stress promoters, acting as a ROS scavenger and independent of its MEK inhibitor function (Ong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%